2022
DOI: 10.1088/1748-9326/ac6ad6
|View full text |Cite
|
Sign up to set email alerts
|

Community-based participatory research for low-cost air pollution monitoring in the wake of unconventional oil and gas development in the Ohio River Valley: Empowering impacted residents through community science

Abstract: Belmont County, Ohio is heavily dominated by unconventional oil and gas development that results in high levels of ambient air pollution. Residents here chose to work with a national volunteer network to develop a method of participatory science to answer questions about the association between impact on the health of their community and pollution exposure from the many industrial point sources in the county and surrounding area and river valley. After first directing their questions to the government agencies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…However, the high number of publications related to the American region as well is not surprising. In fact, the first citizen movements were created in the U.S.A., especially to stress the need of a participatory approach for the oil and gas industry, exploiting the hydraulic fracking of soil [78].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the high number of publications related to the American region as well is not surprising. In fact, the first citizen movements were created in the U.S.A., especially to stress the need of a participatory approach for the oil and gas industry, exploiting the hydraulic fracking of soil [78].…”
Section: Discussionmentioning
confidence: 99%
“…Participants are generally required to attend community activities (like interviews, paper-based surveys, site inspections, etc.) [77,78] or, in recent times, to fill in online questionnaires, accessible through ordinary devices (like smartphones, tablets, etc.) [67,79].…”
Section: Advantagesmentioning
confidence: 99%
“…1). PurpleAir monitors, which employ the Plantower PMS 5003 laser sensors to detect particulate matter, have been used extensively for low-cost monitoring networks, [19][20][21][22] including in Africa, [23][24][25][26] and have demonstrated strong performance when corrected for humidity impacts and calibrated against reference-grade monitoring instrumentation. [27][28][29] The PurpleAir monitoring devices recorded data, including relative humidity, at approximately twominute intervals and the GPS logger recorded every minute.…”
Section: Personal Exposure and Location Monitoringmentioning
confidence: 99%
“…Globally, the population-weighted mean distance to the nearest air quality monitor is 220 km; monitors are especially sparse in Africa. ,, A recent study has shown that only two out of 15 countries under the economic community of West African States (ECOWAS) monitor PM 2.5 pollution . The dearth of PM 2.5 monitoring sensors across African countries has been attributed to the high capital cost of the instruments, as well as the high installation and maintenance cost. PM 2.5 monitors such as Teledyne T640 and MetOne BAM-1020 (β Attenuation Monitor), which have US EPA Federal Equivalent Method status, require high installation, operational and maintenance costs, and are thus not practical to install in the large numbers , that would be necessary to capture the strong spatial and temporal variation in cities. This poses challenges for air quality practitioners in Africa to monitor PM 2.5 levels and subsequently develop policies to control and regulate PM 2.5 pollution.…”
Section: Introductionmentioning
confidence: 99%